1998
DOI: 10.1037/0003-066x.53.6.676
|View full text |Cite
|
Sign up to set email alerts
|

Reward, intrinsic interest, and creativity: New findings.

Abstract: These null results were then presented in Eisenberger and Cameron's (1996) Figure 1, contributing to the illusion of a "normal distribution" of effect sizes, and were later entered into the analyses underlying Figure 2, diluting the mean effect sizes reported there. Note that had the identical six comparisons of reward versus no-reward conditions come from six separate experiments rather than from three factorial experiments, their contributions to Figure 1, and their effects on later analyses, would have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…[18] suggests that 'you can have creativity without innovation, but you cannot have innovation without creativity'. [19] examines the work of a number of researchers such as [20][21][22][23], and points out that there was no definite consensus regarding how creativity is defined. He discovers that the creative process looks different to different researchers.…”
Section: Creativity and Creative Design Products' Definitionmentioning
confidence: 99%
“…[18] suggests that 'you can have creativity without innovation, but you cannot have innovation without creativity'. [19] examines the work of a number of researchers such as [20][21][22][23], and points out that there was no definite consensus regarding how creativity is defined. He discovers that the creative process looks different to different researchers.…”
Section: Creativity and Creative Design Products' Definitionmentioning
confidence: 99%
“…Thus, both studies yielded strong results that were exactly opposite of what the Eisenberger and Cameron model predicts. Eisenberger and Cameron (1998) stated that they had done another meta-analysis in which they compared performancecontingent rewards that had specific performance standards (e.g., rewards for surpassing the 80th percentile) with comparablepositive-feedback control groups, indicating that there were 4 such studies with the free-choice measure and 7 with the self-report measure and reporting that in both cases, these performancecontingent rewards significantly enhanced intrinsic motivation. They did not provide any methodological details, so it is difficult to know what comparisons they made, but there are two important points to keep in mind.…”
Section: The Behavioral Approachesmentioning
confidence: 99%
“…Numerous studies have been carried out on the effect of extrinsic rewards on intrinsic motivation. And although the issue was sometimes fiercely debated (Eisenberger & Cameron, 1998;Hennessey & Amabile, 1998;Lepper, 1998;Sansone & Harackiewicz, 1998), from the available meta-analyses (Cameron & Pierce, 1994;Deci, Koestner, & Ryan, 1999;Deci et al, 2001;Rummel & Feinberg, 1988;Tang & Hall, 1995;Wiersma, 1992) it can be concluded that extrinsic rewards, when they are perceived to have a controlling character, can diminish (intrinsic) motivation (Ryan & Deci, 2000c). Extrinsic motivation was contrasted with intrinsic motivation, which capitalizes on the natural curiosity people possess.…”
Section: Conceptualizations Of Task-specific Motivationmentioning
confidence: 99%